The World Congress of Gastroenterology: Montreal, Quebec, 379 September 12-14, 2005 - Dilip G Patel (Canadian Journal of Gastroenterology)
The World Gastroenterology Organization, or OMGE, is a federation of 93 national societies and associations of gastroenterology representing over 50,000 members worldwide. One of its major missions is to organize and present a World Congress of Gastroenterology (WCOG) every four years. Member societies, just as with Olympic committee members, vote after a formal bidding process and the winner hosts the next meeting. We have received that honour and privilege of hosting the WCOG in Montreal in September 2005. With privilege comes responsibilities, and that goes for every man and woman who cares for the future of gastroenterology in Canada.